International Legal Cooperation in Counter-Terrorism Efforts in Southeast Asia: Challenges and Prospects - Sarocha, Rebecca (PERFECT EDUCATION FAIRY, 2025)
Terrorism remains one of the most pressing threats to security and stability in Southeast Asia, given its transnational character that undermines both national sovereignty and regional peace. This study examines the framework of international legal cooperation in combating terrorism within the ASEAN region, focusing on the ASEAN Convention on Counter-Terrorism (ACCT) of 2007, relevant United Nations conventions, and bilateral as well as multilateral initiatives. Employing a juridical-normative method with a descriptive-analytical approach, the study draws on primary, secondary, and tertiary legal materials to assess the effectiveness and limitations of existing mechanisms. Findings indicate that while ASEAN member states have demonstrated commitment through ratifications and cooperative arrangements, significant challenges persist. These include divergences in national legal systems, sovereignty concerns hindering extradition, limited law enforcement capacity, and the increasing threat of digital radicalization. Despite these obstacles, ASEAN’s collaborative framework serves as a foundation for ongoing dialogue and practical action, highlighting the need for greater harmonization of legislation, enhanced intelligence sharing, and stronger regional as well as global partnerships. The study concludes that adaptive and integrated strategies are essential to strengthen counter-terrorism measures and safeguard long-term regional security.